A new approximation algorithm for fixed points of nonexpansive mappings - Su, Yong Fu; Agarwal, Ravi P. (Mathematical Modelling and Analysis, 2010)
The aim of this paper is to establish a new approximation algorithm for fixed points of nonexpansive mappings in general Banach spaces and to illustrate some numerical results. The approximation algorithm we shall discuss is xt,n = (tT) n x0, where x0 ∈ D(T) is arbitrary, n is a natural number, and t ∈ (0,1). We shall also provide some numerical error estimates. First published online: 09 Jun 2011